Reduced finger tapping speed in patients with schizophrenia and psychomotor slowing: an exploratory fMRI study - Wüthrich, Florian; Zindel, Marc O.; Nadesalingam, Niluja; Nuoffer, Melanie G.; Kyrou, Alexandra; Bernard, Jessica A.; Shankman, Stewart A.; Mittal, Vijay A.; Lefebvre, Stephanie; Walther, Sebastian (Frontiers in Psychiatry, 2025)
IntroductionMotor symptoms are frequent in patients with schizophrenia and have multiple presentations, one of which is psychomotor slowing. Understanding the neural basis of psychomotor slowing may help improve future therapies in schizophrenia. Here, we performed task-fMRI using a finger-tapping task in slowed patients.MethodsThe study included 36 patients with schizophrenia and psychomotor slowing (Salpêtrière-Retardation-Rating-Scale-Score (SRRS) >15), 11 non-slowed patients with schizophrenia, and 33 healthy controls who successfully performed a motor task during fMRI, with four conditions: paced and fast thumb-index finger tapping and thumb alternating finger opposition. The performance was videotaped and taps were counted. We compared task-related neural substrates between groups, task complexity and movement onset.ResultsSlowed patients with schizophrenia showed significantly lower tapping speed than controls in both unpaced conditions (Δ=-.80 (CI=-1.46; -.14)taps/s, p=.019; Δ=-.80 (CI=-1.32; -.28)taps/s, p=.003) while non-slowed patients had a tapping speed between the other two groups.DiscussionIn both task complexity and movement onset factor levels, all the groups activated sensorimotor areas. Slowed patients had no regulation of the task-dependent cerebellar involvement while showing insufficient deactivation of the SPL, pointing to altered recruitment of neural resources in response to motor demands in schizophrenia especially when associated with psychomotor slowing.